Enzymatic inhibitory activity of Ficus deltoidea leaf extract on matrix metalloproteinase-2, 8 and 9 - Abu Bakar, Amirul Ridzuan; Ripen, Adiratna Mat; Merican, Amir Feisal; Mohamad, Saharuddin (Taylor & Francis, 2019)
Dysregulation of matrix metalloproteinases (MMPs) activity is known in many pathological conditions with which most of the conditions are related to elevate MMPs activities. Ficus deltoidea (FD) is a plant known for its therapeutic properties. In order to evaluate the therapeutic potential of FD leaf extract, we study the enzymatic inhibition properties of FD leaf extract and its major bioactive compounds (vitexin and isovitexin) on a panel of MMPs (MMP-2, MMP-8 and MMP-9) using experimental and computational approaches. FD leaf extract and its major bioactive compounds showed pronounced inhibition activity towards the MMPs tested. Computational docking analysis revealed that vitexin and isovitexin bind to the active site of the three tested MMPs. We also evaluated the cytotoxicity and cell migration inhibition activity of FD leaf extract in the endothelial EA.hy 926 cell line. Conclusively, this study provided additional information on the potential of FD leaf extract for therapeutical application. © 2018, © 2018 Informa UK Limited, trading as Taylor & Francis Group.